Geoarchaeological and palaeobotanical evidence for prehistoric cereal storage in the southern Caucasus: the Neolithic settlement of Göytepe (mid 8th millennium BP). (January 2015) - Kadowaki, Seiji; Maher, Lisa; Portillo, Marta; Albert, Rosa M.; Akashi, Chie; Guliyev, Farhad; Nishiaki, Yoshihiro
Abstract: This paper presents direct evidence for cereal storage by Neolithic farmers in west Asia. Storage features analyzed this study are circular clay bins that frequently occur at Neolithic settlements (8th millennium cal. BP) in the southern Caucasus. We examined contexts and uses of clay bin features at the Neolithic settlement of Göytepe (Azerbaijan). We analyzed biogenic microfossil evidence (primarily from phytoliths and dung spherulites) and the sediments of the clay bins through micromorphology, in combination with their associated charred macrobotanical remains. While phytoliths and charred botanical remains indicate direct remnants of stored plants, mainly chaffs, micromorphology and the analyses of faecal spherulites allow us to examine depositional and diagenetic processes of the archaeological sediments inside and outside these features. As a result, one of the clay bins was found to retain deposits at its base exhibiting high concentrations of grass phytoliths with relatively high proportions of inflorescences and low percentages of anatomically connected phytoliths in comparison with its upper fill deposits and areas outside of the bin. These finds, combined with the association of the two complete grinding stones inside the bottom of the bin, suggest that the remains of cereal processing activities, specifically dehusking, may have been placed in the bin. This interpretation is corroborated by the recovery of charred rachises and chaffs of wheat and barley as well as micromorphological observations that the bottommost fill of the bin consists almost entirely of grass phytoliths with few very small charcoal fragments and fine amorphous organic matter. Highlights: We show the first evidence for chaff storage by Neolithic farmers in the Caucasus. We examined depositional processes of Neolithic clay bins in the southern Caucasus. One of the bins is rich in grass inflorescent phytoliths with few other inclusions. Phytolith evidence is consistent with charred wheat and barley remains from the bins. Primary depositional nature is suggested by micromorphology and faecal spherulites.